Use of Celery (Apium graveolens L.) as a Source of Antioxidant in Potato Vermicelli (Solanum tuberosum) : Penggunaan Seledri (Apium graveolens L.) sebagai Sumber Antioksidan pada Bihun Kentang (Solanum tuberosum) - Maria Ulfah; Akhmad Mustofa; Nanik Suhartatik (Agrobiotek, 2024)
Vermicelli is an alternative food to replace rice, a type of noodle that is still in great demand by the public. Vermicelli is a popular food made from rice flour processed through an extrusion process so that it is shaped like a thread. The substitution of potato starch and the addition of celery extract will increase the antioxidant activity content of the vermicelli. The purpose of this research was produce vermicelli which has high antioxidant activity and produce vermicelli with characteristics according to Indonesian National Standard No. 01-2975-2006. Complete Randomized Design factorial with two factors were used in this research. The first factor was the ratio of rice flour and potatoes flour (10:90, 15:85, 20:80). The second factors was the levels of celery extract to water addition of dough (0,78; 1,04; 1,56%). The vermicelli were then tested for moisture content, ash content, crude fiber content and antioxidant activity as well as sensory analysis. The data analyse using Analysis of Variance (ANOVA). The best treatment was on ratio of substitution potatoes flour 20:80(g) with celery extract (0,78%). The fermicelli produced has the following characteristics water 10,65%, ash content 0,52%, fiber content 3,45% and 19,25% antioxidant activity. Femicelli produced in accordance with the quality requirements of SNI No. 01- 2975-2006. The sensory test of fermicelli that having color for dry fermicelli (3,82) color is yellowish dark green, color for wet fermicelli (3.62) is slightly faded green, texture (2,68) is not chewy, after taste (3.36) the taste of celery that lingers after being swallowed and overall preference (3,42).